Major Bleeding Risk in Atrial Fibrillation Patients Co-Medicated With Non-Vitamin K Oral Anticoagulants and Antipsychotics - Chen, Chiung-Mei; Chang, Kuo-Hsuan; Wang, Chun-Li; Tu, Hui-Tzu; Huang, Yu-Tung; Wu, Hsiu-Chuan; Chang, Chien-Hung; Chang, Shang-Hung (Frontiers in Pharmacology, 2022)
Major bleeding risks associated with the non-vitamin K oral anticoagulants (NOACs) use with and without concurrent anti-psychotics in patients with non-valvular atrial fibrillation (AF) were assessed. Totally, 98 863 patients with non-valvular AF receiving at least one NOAC prescription from Taiwan’s National Health Insurance database were enrolled. Major bleeding was defined as a primary diagnosis of intracranial or gastrointestinal hemorrhage or bleeding at other sites. Adjusted incidence rate difference (AIRD) per 1000 person-years and adjusted rate ratio of major bleeding were estimated using Poisson regression and inverse probability of treatment weighting using the propensity score. Events of 8037 major bleeding occurred during 705 521 person-quarters with NOACs prescriptions. Anti-psychotics were used in 26.35% of NOAC-exposed patients. Compared to NOAC use alone, co-medication of either typical (AIRD: 79.18, 95% confidence interval [CI]: 70.63-87.72) or atypical (AIRD: 40.5, 95% CI: 33.64-47.35) anti-psychotic with NOAC had a significant increase in adjusted incidence rate per 1000 person-years of major bleeding. The concomitant use of a NOAC with chlorpromazine (AIRD: 103.87, 95% CI: 51.22-156.52), haloperidol (AIRD: 149.52, 95% CI: 125.03-174.00), prochlorperazine (AIRD: 90.43, 95% CI: 78.55-102.32), quetiapine (AIRD: 44.6, 95% CI: 37.11-52.09) or risperidone (AIRD: 41.55, 95% CI: 22.86-60.24) (All P<0.01) showed a higher adjusted incidence rate of major bleeding than NOACs use alone. Concomitant use of typical (chlorpromazine, haloperidol, or prochlorperazine), or atypical (quetiapine or risperidone) anti-psychotic with NOACs was associated with a significantly increased risk of major bleeding.